Impact of injury location and type of traffic participants on the outcome of traffic accidents in Montenegro - Peličić, Damir; Nedović Vuković, Mirjana (Central European journal of public health, 2025)
OBJECTIVES: The aim of this study was to examine the frequency of fatalities in injuries in traffic accidents in Montenegro, identify contributing risk factors, and determine the most vulnerable participants in these accidents. METHODS: The research was designed as a retrospective descriptive study. Participants were people admitted to the Urgent Centre of Clinical Centre of Montenegro due to injuries in traffic accidents that resulted in serious bodily injury or death in the period from 2011-2020. We presented data using descriptive statistics. The square test was used to examine the association between the outcome of traffic injury with sex, age, category of injury, type of traffic participant, and injury localisation. Additionally, we used logistic regression to estimate the best predictor value of these variables for outcome. RESULTS: It was found that 44.7% of injured people died, the most frequent fatal outcome was registered in patients with central nervous system injuries (73.2%), then in patients with asphyxia (47.0%), and patients with bleeding (40.5%), χ2 = 27.530, p < 0.001. The most frequently injured traffic participants were drivers, but the highest number of deceased were among cyclists. Also, logistic regression showed that the category of injury was the most predictive impact on outcome in traffic-injured correspondents (p < 0.001). CONCLUSION: Among the injured, the highest number are drivers, and the fatal outcome mostly depends on the injury category. Nearly half of those injured in traffic accidents die, especially those with central nervous system injuries and cyclists. Therefore, special attention should be given during public health campaigns related to traffic accident prevention, focusing on this injury and this category of traffic participants.
Keywords: dospělí; Female; dítě; Adult; mladý dospělý; ženské pohlaví; Accidents, Traffic; Adolescent; lidé; Wounds and Injuries; Risk Factors; retrospektivní studie; Male; Aged; Young Adult; rizikové faktory; lidé středního věku; rány a poranění; Černá Hora; Child; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; mladiství; Montenegro; dopravní nehody; Humans